Comparative evaluation of wear resistance surfacing with feeding of nanooxides and nanocarbides to weld pool - V. D. Kuznetsov; D. V. Stepanov (Mechanics and Advanced Technologies, 2020)
The paper presents the results of testing wear resistance of deposited metal, modified by silicon nanooxides and titanium nanocarbides through the weld pool with scheme of its feeding by paraffin rod. It is shown that feeding both nanooxide and nanocarbide to weld pool increase wear resistance of deposited metal up to 4 times. Both nanooxide and nanocarbide feeding to weld pool leads to some changes in the structure increasing martensitic component and, as a result,  hardness of deposited metal. In all the cases of testing the microhardnes of deposited metal, modified by nanocarbides is higher than that with nanooxides. Volume fraction of nonmetallic inclusions is a bit higher in deposited metal, modified by nanooxides and nanocarbides. It is proposed to use paraffin rod as technological scheme of feeding nanocomponents into the weld pool in the surfacing processes. To increase wear resistance of deposited metal, it is recommended in the arc welding surfacing processes to use silicon nanooxide, considering its low price and accessibility on the market .